PERTANGGUNGJAWABAN PIDANA PENGELOLA TEMPAT WISATA AKIBAT KELALAIAN YANG MENGAKIBATKAN WISATAWAN MENGALAMI KECELAKAAN (Studi di Dinas Pariwisata Kabupaten Mandailing Natal) - Efrida Yanti; Marzuki Marzuki; Ibnu Affan (LPPM YPITI, 2021)
With regard to accidents in tourism destinations, if the manager is negligent in managing a tourism destination that can cause accidents, then the manager of the tourist spot due to the negligence can be held liable for crime. The formulation of the problem in this thesis is how to regulate the criminal responsibility of managing tourist attractions due to negligence that causes tourists to have accidents, how is the responsibility of the managers of tourist attractions due to negligence which resulted in tourists having accidents, how are criminal sanctions against managers of tourist attractions due to negligence which resulted in tourists having accidents. The research method used is descriptive analysis which leads to normative juridical legal research, namely research conducted by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the criminal responsibility arrangement for managing tourist attractions due to negligence which resulted in tourists having an accident is regulated in the Criminal Code. The responsibility of the manager of tourist attractions due to negligence which results in tourists having accidents is that they can be held liable for not providing legal protection to tourists as regulated in Article 20 Law No. 10 of 2009. Criminal sanctions against managers of tourist attractions due to negligence which result in tourists having accidents can be imposed as regulated in the Criminal Code while Law Number 10 of 2009 concerning Tourism does not regulate criminal provisions specifically regulating sanctions for managers of tourist attractions in the event of an accident but only regulates that tourists who commit criminal acts may be subject to criminal sanctions.